2008
DOI: 10.1126/science.1155193
|View full text |Cite
|
Sign up to set email alerts
|

Aligning Conservation Priorities Across Taxa in Madagascar with High-Resolution Planning Tools

Abstract: Globally, priority areas for biodiversity are relatively well known, yet few detailed plans exist to direct conservation action within them, despite urgent need. Madagascar, like other globally recognized biodiversity hot spots, has complex spatial patterns of endemism that differ among taxonomic groups, creating challenges for the selection of within-country priorities. We show, in an analysis of wide taxonomic and geographic breadth and high spatial resolution, that multitaxonomic rather than single-taxon ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
386
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 501 publications
(402 citation statements)
references
References 19 publications
3
386
0
13
Order By: Relevance
“…Highest ranked cells include the highest densities (local occurrence levels) of the species with highest weights. The mathematical details and principles of core-area ZONATION are described in Moilanen et al (2005) and Moilanen (2007), and in the ZONATION user manual (Moilanen & Kujala, 2008); illustrative regionalscale examples of the use of core-area ZONATION include Leathwick et al (2008) and Kremen et al (2008).…”
Section: Landscape Prioritization Using Zonationmentioning
confidence: 99%
See 2 more Smart Citations
“…Highest ranked cells include the highest densities (local occurrence levels) of the species with highest weights. The mathematical details and principles of core-area ZONATION are described in Moilanen et al (2005) and Moilanen (2007), and in the ZONATION user manual (Moilanen & Kujala, 2008); illustrative regionalscale examples of the use of core-area ZONATION include Leathwick et al (2008) and Kremen et al (2008).…”
Section: Landscape Prioritization Using Zonationmentioning
confidence: 99%
“…We then limited analysis to the owl and the 130 localized species with 10 or more records remaining after thinning ( Fig. 2) (Kremen et al, 2008;Wisz et al, 2008). The 130 localized species comprised 75 fungi, 21 lichen, 10 bryophytes, eight vascular plants, 12 mollusks, two amphibians, a mammal, and a bird (Table S1).…”
Section: Species Distribution and Environmental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline data was obtained from former Bd surveys Rabemananjara et al 2011). The selection of sites was influenced significantly by the predicted distribution of Bd that overlaps with areas of highest amphibian species richness (Andreone et al 2005) and those identified as in situ conservation priorities for amphibians (Kremen et al 2008).…”
Section: Survey Sitesmentioning
confidence: 99%
“…The 35 designated global biodiversity hotspots cover only 17.3% of earth's land surface, yet contain over 50% of the world's plant species as endemics (Mittermeier et al., 2011; Williams et al., 2011). Within these priority areas, however, smaller‐scale patterns of richness and endemism often are less well understood (Kremen et al., 2008). This represents a significant conservation knowledge gap because many land use decisions are made at the local scale by regional governments, agencies, and private landholders.…”
Section: Introductionmentioning
confidence: 99%